Interpretasi guru agama sebagai role model dalam mengintegrasikan karakter religius peserta didik - Azmi; Sarwan Mukaffan (Fukuri: Journal of Psychology, 2025)
Teachers have an important role in shaping students' character because the teacher is a figure who holds a strategic position in providing teaching both in the classroom and outside the classroom. Moreover, PAI teachers where religious education has a big role in shaping students' religious character. As educators who interact directly in the learning process, religious teachers hold a position as role models in building this character. Through a qualitative approach, this research analyzes the efforts made by teachers starting from how PAI teachers' behavior, attitudes and actions can influence the formation of students' religious character at school. The results of the research show that religious teachers demonstrate exemplary spiritual life, religious discipline and good morals so that they can have a positive influence and provide a foundation for students to control their behavior. Religious teachers not only teach theoretical material, but also serve as examples in applying religious values in life. Various efforts were also made, such as getting into the habit of praying, reading the Asmaul Husna together, integrating the values of tolerance and respecting each other's opinions, acting politely, getting used to praying in congregation, and using the story method.